TECHNICALLY AND ECONOMICALLY FEASIBLE HYDRO POTENTIAL OF SMALL RIVERS IN SERBIA - Stevović, Svetlana (Termotehnika, 2017)
As a renewable energy source that is environmentally friendly and cost-effective, the hydropower potential of Serbia represents a valuable common good and notable economic force in a development strategy of the country. It is an important component of the country’s overall energy balance, both at present and in the future. Seventy-seven percent of the hydropower potential of Serbia is technically and economically usable, based on the present energy situation in the country, the latest technical advances, and economic criteria. Out of this amount, eight percent could be generated in small-scale hydropower plants, with an installed capacity less than 10 MW. In order to promote acquisition of Green Certificates, stimulate the Clean Development Mechanism (CDM) projects and facilitate the Certified Emission Reduction (CER) trading, Serbia is shifting its development strategy towards renewable energy sources, particularly small-scale HPPs. The necessary project documentation has been prepared, nearly 1,000 potential locations for small-scale HPPs have been identified, and the legislative framework is being synchronized with a world-accepted practice in this field. This paper presents some technical possibilities for the construction of small-scale HPPs in Serbia. The attention is focused on the specific conditions, statistical parameters, and the legislative framework of the country.